Exploration of Actinomycetes from Krueng Aceh River Estuary Sediments for Antibacterial Compounds - Harahap, Diannita; Wahyuni, Rosi (Universitas Brawijaya, 2025)
Actinomycetes are major producers of various classes of antibiotics, including those that work against both Gram-positive and Gram-negative bacteria. River sediments have varying physical and chemical conditions and a source of highly complex material that is suitable for the growth of Actinomycetes. This study investigated the characteristics and genus of Actinomycetes from the Krueng Aceh Estuary sediments and their ability to produce antibiotics. Sediment samples were collected from the Krueng Aceh estuary using a purposive sampling method. The isolates were cultured on Yeast Malt Extract Agar (YMA) and identified based on morphological characteristics and biochemical tests. Antibacterial screening was conducted using the well diffusion method against Staphylococcus aureus and Escherichia coli. Environmental parameters, including current speed, salinity, dissolved oxygen (DO), pH, and temperature, were measured in-situ to characterize the habitat. The research identified six isolates belonging to the genera Streptomyces and Nocardia. Antibiotic activity tests using the well diffusion method revealed varying degrees of growth inhibition of against the test bacteria. Streptomyces sp.A3 demonstrated strong antibacterial activity against E. coli with an inhibition diameter area of 15.86 mm, while Streptomyces sp.A4 showed moderate activity of 4.12 mm. In addition to the tested S. aureus, Streptomyces sp.A2 exhibited the strongest antibacterial activity, showing an inhibition diameter of 16.56 mm, and Streptomyces sp.A3 showed moderate activity (4.42 mm). This study concludes that Streptomyces isolated from the Krueng Aceh river estuary possesses the potential to produce antibacterial compounds capable of inhibiting the pathogenic bacteria S. aureus and E. coli.